Understanding shared decision-making experience among vulnerable population: Focus group with food bank clients. Issue 1 (25th August 2020) - Lee, Young Ji; Brazile, Tiffany; Galbiati, Francesca; Hamm, Megan; Bryce, Cindy; Jain, Sandeep; Kraschnewski, Jennifer; McTigue, Kathleen
Abstract: Introduction: Shared decision-making (SDM) is a critical component of delivering patient-centered care. Members of vulnerable populations may play a passive role in clinical decision-making; therefore, understanding their prior decision-making experiences is a key step to engaging them in SDM. Objective: To understand the previous healthcare experiences and current expectations of vulnerable populations on clinical decision-making regarding therapeutic options. Methods: Clients of a local food bank were recruited to participate in focus groups. Participants were asked to share prior health decision experiences, explain difficulties they faced when making a therapeutic decision, describe features of previous satisfactory decision-making processes, share factors under consideration when choosing between treatment options, and suggest tools that would help them to communicate with healthcare providers. We used the inductive content analysis to interpret data gathered from the focus groups. Results: Twenty-six food bank clients participated in four focus groups. All participants lived in areas of socioeconomic disadvantage. Four themes emerged: prior negative clinical decision-making experience with providers, patients preparing to engage in SDM, challenges encountered during the decision-making process, and patients' expectations of decision aids. Participants also reported they were unable to discuss therapeutic options at the time of decision-making. They also expressed financial concerns and the need for sufficiently detailed information to evaluate risks. Conclusion: Our findings suggest the necessity of developing decision aids that would improve the engagement of vulnerable populations in the SDM process, including consideration of affordability, use of patient-friendly language, and incorporation of drug–drug and drug–food interactions information.